1987
DOI: 10.1093/ajcn/46.4.659
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxine supplementation: effect on lymphocyte responses in elderly persons

Abstract: The effect of pyridoxine supplementation on lymphocyte responsiveness was investigated in 15 persons aged 65-81 y. Eleven subjects received 50 mg/d pyridoxine HCl (PN). Four subjects received a placebo. Lymphocyte proliferation to T and B cell mitogens, lymphocyte subpopulations with monoclonal antibodies, and plasma pyridoxal 5'-phosphate (PLP) were measured before and after 1 and 2 mo of supplementation. After 1 and 2 mo plasma PLP levels increased by 195 +/- 88 nM and 201 +/- 84 nM, respectively, in subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(44 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…In the present study, our critically ill patients had abnormal immune responses even though their vitamin B 6 intake was higher than Taiwan DRI recommendations (Department of Health, Taiwan, 2002) on the first day of admission to the ICU. In agreement with the previous studies (Casciato et al, 1984;Talbott et al, 1987;Folkers et al, 1993), several cellular immune response parameters (i.e., T lymphocyte, T-helper and T-suppressor cells) significantly increased after the supplementation of either 50 or 100 mg/day of vitamin B 6 for 14 days; whereas immune responses showed no significant changes in the control group. This suggests that vitamin B 6 supplementation could increase immune responsiveness of only T cells but not B cells.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, our critically ill patients had abnormal immune responses even though their vitamin B 6 intake was higher than Taiwan DRI recommendations (Department of Health, Taiwan, 2002) on the first day of admission to the ICU. In agreement with the previous studies (Casciato et al, 1984;Talbott et al, 1987;Folkers et al, 1993), several cellular immune response parameters (i.e., T lymphocyte, T-helper and T-suppressor cells) significantly increased after the supplementation of either 50 or 100 mg/day of vitamin B 6 for 14 days; whereas immune responses showed no significant changes in the control group. This suggests that vitamin B 6 supplementation could increase immune responsiveness of only T cells but not B cells.…”
Section: Discussionsupporting
confidence: 92%
“…However, the effect of vitamin B 6 supplementation on immune responses in immunocompromised subgroups within the population (i.e., elderly, ill patients) has been seldom reported. Only a few studies have shown that 50-300 mg/day vitamin B 6 supplementation in either healthy elderly or hemodialysis patients significantly improved immune responses of subjects (Casciato et al, 1984;Talbott et al, 1987;Folkers et al, 1993). In the present study, our critically ill patients had abnormal immune responses even though their vitamin B 6 intake was higher than Taiwan DRI recommendations (Department of Health, Taiwan, 2002) on the first day of admission to the ICU.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Critical clinical conditions and complex metabolism in the critically ill may account for the reduction of plasma PLP and PL. Since vitamin B6 is required for normal nucleic acid and protein synthesis and for cellular multiplication, vitamin B6 deficiency causes profound effects on immune system function (Axlerod 1971;Talbott et al, 1987). Dietary or supplemented vitamin B6 intake is suggested for hospitalized patients.…”
Section: Resultsmentioning
confidence: 99%